Marauder speed: "Getting you there faster" - Thorson, M. (Track Coach, 2018)
The objective of this speed presentation is to provide a practical and simple guide to speed and speed development. It is our goal that we can provide both coaches and athletes alike a basic, yet somewhat technical understanding of speed and what is required to develop and enhance it.